2010
DOI: 10.1158/1078-0432.ccr-09-2902
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 and IDH2 Mutations Are Prognostic but not Predictive for Outcome in Anaplastic Oligodendroglial Tumors: A Report of the European Organization for Research and Treatment of Cancer Brain Tumor Group

Abstract: Purpose: Recent studies have shown the prognostic significance of IDH1 mutations in glioma. It is yet unclear if IDH1 mutations are predictive for outcome to chemotherapy. We determined the effect of IDH1 mutations on progression-free survival and overall survival (OS), and its correlation with other clinical and molecular features in the prospective randomized European Organization for Research and Treatment of Cancer study 26951 on adjuvant procarbazine, 1-(2-chloroethyl)-3-cyclohexyl-L-nitrosourea, and vinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
224
5
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 364 publications
(251 citation statements)
references
References 25 publications
17
224
5
5
Order By: Relevance
“…Several clinical predictors of survival have been identified, such as age, preoperative functional status, and tumor extent 22. In addition, some genetic and epigenetic features may be used as prognostic factors 2, 3. Nevertheless, despite many efforts to treat this disease, the mortality rate remains high, recurrence seems to be the rule, and still the outcome is invariably fatal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical predictors of survival have been identified, such as age, preoperative functional status, and tumor extent 22. In addition, some genetic and epigenetic features may be used as prognostic factors 2, 3. Nevertheless, despite many efforts to treat this disease, the mortality rate remains high, recurrence seems to be the rule, and still the outcome is invariably fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Putative genetic and epigenetic prognostic factors have been investigated in order to optimize treatment strategies. These include 1p/19q codeletion, isocitrate dehydrogenase (IDH) 1 and 2 gene ( IDH1/2 ) mutations, and methylation of the O(6)‐methylguanine‐DNA methyltransferase (MGMT) promoter 2, 3, which confer a better responsiveness to radio‐ and chemotherapy 4, 5, 6, even the disease is still incurable. A prominent feature of GBM is the aberrant angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…All three markers are considered as indicators of favorable prognosis. [6][7][8][9] MGMT hypermethylation status is already included in the nomogram for predicting survival of patients with newly diagnosed glioblastoma, and IDH1/2 mutation was shown to be a reliable genetic marker of secondary glioblastomas and their precursor lesions. [10][11][12] In contrast, the presence of other markers such as loss of PTEN and CDKN2A and amplification of EGFR are reported to be indicative for more aggressive tumor behavior.…”
mentioning
confidence: 99%
“…In this context, identification of mutations in the isocitrate dehydrogenase (IDH1/ IDH2) either in the R132 or R172 residues were recently highlighted, and has already become a molecular marker of significant diagnostic and prognostic relevance in the assessment of human gliomas (Parsons et al, 2008;Yan et al, 2009). Mutations of the IDH1 R132 are reported in 55-80% of grade II/III oligodendroglioma/astrocytomas, over 90% of secondary glioblastomas (GBMs), rarely in primary glioblastoma (Van den Bent et al, 2010), and are associated with favorable prognosis (Uno et al, 2011). In contrast IDH2 mutations are rare, but more common in oligodendroglial tumors, as compared to astrocy¬tomas (Raynaud et al, 2010 protective mechanism in glioma patients which could be the reason for better outcome in patients with mutant IDH than those with the wild-type IDH genes (Zhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast IDH2 mutations are rare, but more common in oligodendroglial tumors, as compared to astrocy¬tomas (Raynaud et al, 2010 protective mechanism in glioma patients which could be the reason for better outcome in patients with mutant IDH than those with the wild-type IDH genes (Zhu et al, 2011). Most of the available studies on IDH1 and 2 mutations are reported from western countries (Bleeker et al, 2009;Metellus et al, 2010;Van den Bent et al, 2010;Cykowski et al, 2012), few reports from Asia (Mukasa et al, 2012;Song Tao et al, 2012), while there is only one report of IDH1 mutations in Indian glioma patients (Jha et al, 2011). In the current study we evaluated IDH1 and IDH2 mutations in glioma patients of different histological types and grades with the aim of assessing their frequency, distribution pattern and their correlation with clinicopathological findings.…”
Section: Introductionmentioning
confidence: 99%